PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI SISTEM PERNAPASAN MANUSIA - Alfany, Zikrina Caesaria; Purnomo, Aris Rudi (PENSA E-JURNAL: PENDIDIKAN SAINS, 2023)
This study aimed at improving students’ critical thinking skills through the application of the guided inquiry model in learning material about the human respiratory system. This study was conducted at a junior high school in Surabaya, including 24 class VII-A students. The study carried out was pre-experimental and used a one group pretest-posttest design. This study data was collected through a written test consisting of a pretest and posttest, as well as a questionnaire. The instruments used in this study include pretest and posttest sheets, as well as student response questionnaires. Data analysis was carried out using descriptive statistics and inferential statistics (Wilcoxon Sign Rank Test). The results of the study show that students’ critical thinking abilities have increased after implementing guided inquiry-based learning. This is supported by the average N-Gain score of 0.63, and the average response questionnaire results of 84% are in the very good category.